Desenvolvimento de plataforma de analytics para comercialização de informações estruturadas - Furquim Junior, Claudio (2019)
Itreports the process of implementing a data-based product, innovative for the company B3, since its data were being made available free of charge, from the identified opportunity of marketing information Made available in interactive visualization panels (dashboards), taking advantage of the data generated by the company, with the aim of obtaining a new source of revenue for the company. For this, initial market research was conducted to identify the ad-herence of the new product to customers in the financial market: Brokers, value distributors, investment banks, and retail. In parallel, the resources needed to develop this new product were identified in the company. Through the technologies available in the market, such as data virtualization, and with analyses developed by several teams involved in this project, a new product has been built that provides Information for the financial market by visualization tools, also known as dashboards, significantly reducing the complexity of the query. After im-plementation, it can be observed its applicability, because not only has there been good ac-ceptance by the target audience, but also organized a new data culture in B3, which has been spreading through its various departments and companies demanding new Projects inthis theme due to the fact that this project creates and now as a legacy provide infrastructure for data projects.